Does Fintech Lending Disrupt Consumer Lending From Commercial Bank? Evidence From Listed Bank In Indonesia - Iskandar, Muhammad Ikbal; Rokhim, Rofikoh (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aims to analyze the impact of fintech lending financing on commercial banks' distribution of consumer credit in Indonesia. We use panel data regression with random effects from 32 commercial banks listed on the Indonesia Stock Exchange as of September 2023. The distribution of consumer credit from these banks accounts for more than 70% of Indonesia's total consumer credit distribution. The study's results indicate that fintech lending grows simultaneously with commercial banks' consumer credit, suggesting a complementary relationship. The result is supported by commercial banks' distribution of consumer credit through channeling schemes to fintech lending. However, the outstanding value of such channeling credit remains limited, hence it is yet to be significant. Based on bank ownership, fintech lending competes with private banks in KBMI 1 as they target the same segmentation. The study concludes that, generally, fintech lending does not disrupt the distribution of consumer credit by incumbents.